2018
DOI: 10.3390/en11041003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wall Boundary Layer Thickness on Power Performance of a Recirculation Microbial Fuel Cell

Abstract: Abstract:Hydrodynamic boundary layer is a significant phenomenon occurring in a flow through a bluff body, and this includes the flow motion and mass transfer. Thus, it could affect the biofilm formation and the mass transfer of substrates in microbial fuel cells (MFCs). Therefore, understanding the role of hydrodynamic boundary layer thicknesses in MFCs is truly important. In this study, three hydrodynamic boundary layers of thickness 1.6, 4.1, and 5 cm were applied to the recirculation mode membrane-less MFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…This indicates that the increasing flow rate delays biofilm formation to some degree. This result differs from other studies with EAB that found the startup time to decrease when convective flow was applied . However, studies of biofilm formation under defined flow conditions suggest that the influence of shear forces on biofilm growth can be both beneficial or detrimental to biofilm formation depending on the limiting factor for biofilm growth considering the environmental conditions .…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…This indicates that the increasing flow rate delays biofilm formation to some degree. This result differs from other studies with EAB that found the startup time to decrease when convective flow was applied . However, studies of biofilm formation under defined flow conditions suggest that the influence of shear forces on biofilm growth can be both beneficial or detrimental to biofilm formation depending on the limiting factor for biofilm growth considering the environmental conditions .…”
Section: Resultscontrasting
confidence: 98%
“…On a microscopic scale, the flow of the culture medium can facilitate mass transfer through the biofilm and it is thus expected to affect EAB performance to some degree . An increase in performance of EAB has been reported in several studies when the biofilms were subjected to defined shear stresses . Additionally, shear forces can influence biofilm thickness and morphology by inducing the detachment of biomass from the biofilm surface and the production of extracellular polymeric substances favoring the formation of thinner and more concentrated biofilm structures .…”
Section: Introductionmentioning
confidence: 99%
“…They are used to determine the operative conditions under load (external resistance). The polarization curves are usually used to identify four important losses: (i) fuel crossover losses due to the depletion of fuel passing through the electrolyte; (ii) activation losses due to slow reaction kinetics on the surface of the electrodes; (iii) ohmic losses due to the resistance present for the flow of electrons and ions through electrodes and electrolytes, respectively; and (iv) the concentration losses due to the changes in reactant concentrations on the electrode surfaces [15,16].…”
Section: Effects Of Flowing Electrolyte Parameters On Zafc Power Perfmentioning
confidence: 99%
“…Microbial fuel cell studies were also being investigated thoroughly. The effect of the hydrodynamic layer thickness was found to be significant on the voltage and charged transfer resistance [26]. In another study, the calcination temperature on the cathodic chambers was studied and it was found that the electrode synthesized at 500 • C could degrade oily wastewater up to 99.3% [27].…”
mentioning
confidence: 99%
“…This Special Issue of Energies on the subject of "Biofuel and Bioenergy Technology" contains the successful invited submissions . A total of twenty-seven technical papers which cover diversified biofuel and bioenergy technology related researches have shown critical results and contributed significant findings in biomass processing [1,2], bio-oil and biodiesel [3][4][5][6][7][8][9][10][11], syngas [12][13][14], biogas/methane [15][16][17][18][19], bioethanol and alcohol-based fuels [20][21][22], solid fuel [23][24][25] and also microbial fuel cell [13,26,27] developments.…”
mentioning
confidence: 99%